EVALUASI KESESUAIAN LAHAN BEKAS TAMBANG TIMAH UNTUK BUDIDAYA KELAPA SAWIT - Gurnito, Genia; Taryana, Didik (Departemen Tanah, Fakultas Bio-industri Pertanian dan Kehutanan, Universitas Brawijaya, 2026)
Tin mining is a daily activity carried out by some of the people in Lampur Village. Mining activities have an impact on the land that is left behind in the form of a decline in land quality. Land evaluation is needed to identify the potentials and constraints that exist in an area. The approach applied in this study involved matching primary and secondary data with the criteria for oil palm growth and development. Primary data were obtained by conducting laboratory analyses of cation exchange capacity (CEC), texture, pH, base saturation, and salinity. Secondary data included humidity, temperature, and rainfall. The results of the analysis show that former tin mining land is actually classified as unsuitable or N with texture as a constraint. The soil texture at 10 points is dominated by a sand fraction of 98%, causing the soil at the study site to be coarse in texture and requiring improvement efforts. Temperature (tc) is a permanent constraint that cannot be improved because it is natural. Constraints such as oxygen availability (oa), nutrient retention (nr), and erosion hazard (eh) can be improved to enhance land quality and class. Potentially, former tin mining land can be improved through remediation efforts, thereby increasing land quality while considering certain limiting factors.